Psychosocial predictors of early postpartum depressive and anxious symptoms in primiparous women and their partners - Erin J. Henshaw; Marie Cooper; Teresa Wood; Stacey N. Doan; Sanchita Krishna; Marie Lockhart (BMC, 2023)
Abstract Background While the majority of research on postpartum depressive and anxious symptoms has focused on mothers, a growing body of research suggests a need to understand the role of the partner's health and relationship quality as predictors of postpartum maternal depression, while also better understanding correlates of partner or paternal depression in the postpartum period. The purpose of the current study is to evaluate mother and partner stress, anxiety, mood, infant care support, and relationship quality as predictors of perinatal depressive and anxious symptoms in first time mothers and partners during the postpartum hospital stay. Methods First time parent couples (n = 116) completed a survey during the two-day postpartum stay in a Midwest hospital. Depressive (EPDS) and anxiety symptoms (DASS-21-Anxiety) were assessed in both mothers and partners. Hierarchical linear regression was used to evaluate relationship satisfaction, partner infant care support, stress, and co-parent mood as predictors of mood in mothers and partners separately. Results Stress was a predictor of anxiety and depression symptoms in both mothers and partners. Additionally, co-parent anxiety significantly predicted anxiety in both mothers and partners. Maternal relationship satisfaction was a predictor of the partner's depressive symptoms, and maternal perceptions of partner infant support predicted maternal depressive symptoms. Conclusions Together, these results suggest that stress, relationship satisfaction, and co-parent mood are related to depressive and anxious symptoms in mothers and partner, underscoring the need to continue exploring mother and partner mental health in a dyadic framework.